Sabrina [videorecording (DVD)] - Wilder, Billy, 1906-2002; Bogart, Humphrey, 1899-1957; Hepburn, Audrey, 1929-1993; Holden, William, 1918-1981 (Paramount Home Entertainment, 2008)
David and Linus are brothers running the family corporation. When the chauffeur's daughter comes back from Paris she finds she has the attention of David, whom she has always liked, but starts to fall in love with Linus. Includes bonus features.